Advanced lectures on machine learning revised lectures - Bousquet Olivier ed.; ML Summer Schools 2003; ML summer schools 2003 Canberra, Australia 2-14 Feb 2003 (Berlin Springer-Verlag, 2004)
This book presents revised lectures of two subsequent summer schools held in 2003 in Canberra, Australia, and in T ingen, Germany. The tutorial lectures included are devoted to statistical learning theory, unsupervised learning, Bayesian inference, and applications in pattern recognition; they provide in-depth overviews of exciting new developments and contain a large number of references.
Keywords: Machine learning